Pengaruh Kegiatan Outdoor Drumband Terhadap Keterampilan Fisik Motorik Anak Usia Di TK Hang Tuah Kota Bengkulu - Welia Nadillah; Nelly M; Budrianto B (UIN Fatmawati Sukarno Bengkulu, 2026)
This research was motivated by the fact that the development of physical motor skills of early childhood children at TK Hang Tuah Bengkulu City has not developed optimally. This can be seen from several children who still experience difficulties in maintaining body balance, coordinating hand and foot movements, and following movements during physical activities. One of the activities that can stimulate children's physical motor development is outdoor drumband activities, because this activity involves body movements, coordination, balance, and the ability to play musical instruments simultaneously.This study aims to determine the effect of outdoor drumband activities on the physical motor skills of children aged 5–6 years at TK Hang Tuah Bengkulu City and to determine the improvement of children's physical motor skills after being given outdoor drumband activities.This research used a quantitative approach with an experimental method and a One Group Pretest-Posttest Design. The population in this study consisted of all children aged 5–6 years who participated in outdoor drumband activities at TK Hang Tuah Bengkulu City. The sample was taken using a saturated sampling technique, in which all members of the population were used as research samples. Data collection techniques were carried out through observation using physical motor skill assessment sheets. The treatment in the form of outdoor drumband activities was conducted for approximately four weeks with a frequency of twice a week.The results of the study indicate that outdoor drumband activities have an effect on the physical motor skills of early childhood children at TK Hang Tuah Bengkulu City. After participating in outdoor drumband activities, children's abilities improved in maintaining balance, coordinating hand and foot movements, changing positions, playing drumband instruments, and following movement instructions. This shows that outdoor drumband activities can be an effective and enjoyable learning activity to stimulate the physical motor development of early childhood children.